The Lost Identity of Izmir - Tanis, Fatma (International Planning History Society Proceedings, 2016)
Port cities are distinguished from other cities by their waterfronts, which were shaped by economic and cultural transactions between each city and its networks. Trade-related activities prepared the conditions for accelerated globalisation with economic changes. The Ottoman Empire supported commerce and production in Western Anatolia after 16th century. Many European merchants thus moved to Izmir in accord with an agreement made by the Ottoman Empire in order to maintain commercial events. Afterwards, the city developed as a culturally diverse entity due to its port activity. The waterfront and arguably the whole structure of the city have been influenced by cross cultural exchanges. Study explains how shifting networks have created a unique palimpsest of structures and actor networks between 16th and 21st century in Izmir, a port city on western coast in Turkey. This paper explores the transformation of Izmir’s urban form and identity. Different architectural practices such as Dutch, British, French, Italian, Greek were concretised on Izmir’s waterfront and have become a part of the city’s identity. Nevertheless, political decisions, governmental policies, fires, earthquakes, planned and unplanned events changed the waterfront and caused gaps in history told by its built environment. This study analyses the vicissitudes in the planning history of Izmir’s waterfront.